Distribution of poly(A)-containing RNA during normal pollen development and during induced pollen embryogenesis in Hyoscyamus niger (The Rockefeller University Press, 1981)
The distribution of poly(A)-containing RNA [poly(A)+RNA] in pollen grains of Hyoscyamus niger during normal gametophytic development and embryogenic development induced by culture of anther segments was followed by in situ hybridization with [3H]-polyuridylic acid as a probe. No binding of the isotope occurred in pollen grains during the uninucleate phase of their development. Although [3H]polyuridylic acid binding sites were present in the generative and vegetative cells of maturing pollen grains, they almost completely disappeared from mature grains ready to germinate. During pollen germination, poly(A)+RNA formation was transient and was due to the activity of the generative nucleus, whereas the vegetative nucleus and the sperm cells failed to interact with the applied probe. In cultured anther segments, moderate amounts of poly(A)+RNA were detected in the uninucleate, nonvacuolate, embryogenically determined pollen grains. Poly(A)+RNA accumulation in these grains was sensitive to actinomycin D, suggesting that it represents newly transcribed mRNA. After the first haploid mitosis in the embryogenically determined pollen grains, only those grains in which the generative nucleus alone or along with the vegetative nucleus accumulated poly(A)+RNA in the surrounding cytoplasm were found to divide in the embryogenic pathway. Overall, the results suggest that, in contrast to normal gametophytic development, embryogenic development in the uninucleate pollen grains of cultured anther segments of H. niger is due to the transcriptional activation of an informational type of RNA. Subsequent divisions in the potentially embryogenic binucleate pollen grains appeared to be mediated by the continued synthesis of mRNA either in the generative nucleus or in both the generative and vegetative nuclei.